A STUDY ON POSITIVE AND NEGATIVE IMPACT ON SOCIAL MEDIA ADDICTION FOR SCHOOL GOING CHILDREN - A.PUSHPA , Dr. A. MUTHULAKSHMI (South Eastern European Journal of Public Health, 2025)
The present study aims to identify the positive and negative impact on social media addicition for school going children. Social media has become an integral part of contemporary life, profoundly influencing the behavior and development of school-going children. This study explores the positive and negative impacts of social media addiction on children aged 10 to 18. On the positive side, the research examines how social media fosters creativity, enhances communication skills, and provides educational resources. Conversely, it delves into the adverse effects, such as academic distraction, cyberbullying, diminished face-to-face interactions, and mental health challenges like anxiety and depression.The objective of the study was used to assess the positive and negative impacts of social media on the respondents. To measure the social media addiction among the respondents. The final sample size was 380 students after scrutinizing the collected data for completeness and accuracy. The findings reveal a nuanced relationship between social media usage and its effects, emphasizing the role of parental supervision and digital literacy in mitigating risks. The study concludes by recommending strategies to balance the advantages of social media while curbing its negative consequences, highlighting the importance of awareness campaigns, digital detox programs, and a structured regulatory framework. This research aims to contribute to the growing discourse on responsible social media usage and its implications for the holistic development of children.